2016
DOI: 10.1016/j.yjmcc.2016.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-activated phosphodiesterase 1A is highly expressed in rabbit cardiac sinoatrial nodal cells and regulates pacemaker function

Abstract: Constitutive Ca2+/calmodulin (CaM)-activation of adenylyl cyclases (ACs) types 1 and 8 in sinoatrial nodal cells (SANC) generates cAMP within lipid-raft-rich microdomains to initiate cAMP–protein kinase A (PKA) signaling, that regulates basal state rhythmic action potential firing of these cells. Mounting evidence in other cell types points to a balance between Ca2+-activated counteracting enzymes, ACs and phosphodiesterases (PDEs) within these cells. We hypothesized that the expression and activity of Ca2+/Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 69 publications
1
37
0
Order By: Relevance
“…Reports on its importance relative to other PDE families and the relative expression of the three PDE1 subfamilies in different animal species have not been consistent (Table A in S1 File )[ 62 74 ]. Overall, our findings agree with some but not all published studies: i) PDE1 accounts for a large proportion of cAMP-PDE activity in the heart [ 65 67 , 70 ]; ii) The protein expression of PDE1C is much higher than that of PDE1A in the myocardium [ 63 , 64 , 67 , 72 74 ]; iii) Therefore, PDE1C is likely more important for cardiac hypertrophy than PDE1A; iv) The protein expression of PDE1A is much higher in adult aorta [ 32 , 47 , 75 ]; v) Consistent with this pattern of expression, Pde1a knockout mice in our study had lower blood pressures and a hyperdynamic circulation with an increased heart rate and ejection fraction. Interestingly, a large gene-centric meta-analysis in 87,736 individuals of European ancestry has identified an association between the PDE1A locus and diastolic and mean arterial pressures [ 76 ], and mutations of PDE3A resulting in increased PKA–mediated PDE3A phosphorylation and gain of function have been found in six families with hypertension and brachydactily syndrome [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on its importance relative to other PDE families and the relative expression of the three PDE1 subfamilies in different animal species have not been consistent (Table A in S1 File )[ 62 74 ]. Overall, our findings agree with some but not all published studies: i) PDE1 accounts for a large proportion of cAMP-PDE activity in the heart [ 65 67 , 70 ]; ii) The protein expression of PDE1C is much higher than that of PDE1A in the myocardium [ 63 , 64 , 67 , 72 74 ]; iii) Therefore, PDE1C is likely more important for cardiac hypertrophy than PDE1A; iv) The protein expression of PDE1A is much higher in adult aorta [ 32 , 47 , 75 ]; v) Consistent with this pattern of expression, Pde1a knockout mice in our study had lower blood pressures and a hyperdynamic circulation with an increased heart rate and ejection fraction. Interestingly, a large gene-centric meta-analysis in 87,736 individuals of European ancestry has identified an association between the PDE1A locus and diastolic and mean arterial pressures [ 76 ], and mutations of PDE3A resulting in increased PKA–mediated PDE3A phosphorylation and gain of function have been found in six families with hypertension and brachydactily syndrome [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basal PDE degradation of cAMP in rabbit SAN myocytes has been shown to modulate and compartmentalize Ca 2+ -clock mechanisms such as RyR and PLB, as PDE inhibition increases the rate and amplitude of local Ca 2+ releases (Vinogradova et al, 2008). This has been confirmed specifically for PDE1A in rabbit SAN myocytes, facilitated by its higher expression in the SAN compared to other regions of the heart (Lukyanenko et al, 2016). Although inhibition of single PDEs only moderately increases SAN myocyte firing, recently it has been shown that dual PDE3 and PDE4 inhibition synergistically increases basal SAN firing rate by ∼50% (Vinogradova et al, 2018a).…”
Section: Intracellular Compartmentalizationmentioning
confidence: 70%
“…In cardiomyocytes, PDE1C shows a predominantly cytosolic distribution, localising to the M-and Z-lines of the sarcomere, and is present in microsomal fractions [55]. PDE1A protein is abundant in rabbit sinoatrial (SA) node cells where it is purported to moderate pacemaker activity [59], but whether it functions in an analogous capacity in human hearts is currently unknown. Similarly, whilst PDE1A appears to regulate cell death in vascular smooth muscle cells (VSMCs) [60], a corresponding cardiac-specific role is not established.…”
Section: Cardiac Physiologymentioning
confidence: 99%